Teachers' and students' perception on using local-contents in English textbooks in EFL context - Alexon, Alexon; Safnil, Safnil; Syafryadin, Syafryadin (LPMPP Universitas Negeri Yogyakarta, 2024)
English textbook that contains local content can be considered more interesting and easier to understand and use by students and teachers. Therefore, this study aims to analyze teachers and students' perception on using local-content English textbook for senior high school. This study employed mixed-method research by involving 37 seven certified English teachers who had 10 years or above experiences in teaching English in senior high schools in Bengkulu and 100 students. The instruments of this study were questionnaire and interview guideline. The quantitative data were analyzed by using descriptive statistics, while the qualitative data were analyzed by using eduction, displaying and conclusion. The result showed that teachers had positive perception on using Bengkulu local content English textbooks. It can be proved by looking at the majority of English teachers answered strongly agree and agree in the questionnaire. Another result indicated that students gave positive responses on local textbook which covers Bengkulu culture. It can be seen that most of students were happy to see the pictures or other things related to Bengkulu local culture in English textbook. In short, English textbook with local content is essential to be used for students and teachers because it would encourage students to learn English.